Solder fatigue failures in a new designed power module under Power Cycling - Durand, C.; Klingler, M.; Bigerelle, M.; Coutellier, D. (Microelectronics and reliability, 2016)
Today a point has been reached where lifetimes of power modules are limited by the standard packaging technologies, such as wire bonding. To surpass these limits, a new power module was designed using Cu clips as interconnects instead of Al wire bonds. With this new design the structure robustness should be improved and lead to a reliability gain but in counterpart it requires an additional solder layer in order to fix the clip onto the die. This paper studies the failure mechanisms occurring in these two solder layers under power cycling. The behavior of solder layers is precisely analyzed by performing power cycling tests and by taking advantage of Finite Elements simulations. Furthermore an experimental and numerical sensitivity study on test parameters is conducted. Results obtained enable the definition of solder lifetime prediction models. •Cracks in bottom and top solder are propagating toward chip center•Solder meniscus are critical areas in terms of creep failure•A sensitivity study on test parameters is conducted for the top and bottom solder•Lifetime models are defined for the top and bottom solder•Top solder failure is less critical for the module than bottom solder failure